Sistem informasi SPJ berbasis web dengan metode Agile di Dinas Keuangan Papua Barat - Setiyawan, Yesaya; Marini , Lion Ferdinand; Baisa , Lorna Yertas (AITI, 2025)
This study builds an internet-accessible Accountability Letter Information System (SI SUPER) for the Finance Office of West Papua Province. The goal is to speed up the process of making a Disbursement Order (SP2D), overcome the spread of hardcopy files, and provide quick access to important documents. Development using the Agile method consists of the stages of requirements, design, development, testing, and implementation. The SI SUPER application enables submission of Fund Disbursement Orders (SP2D), creation of SP2D by managers, and archiving of other key documents. The application is also equipped with features for administrators, financial managers, and Regional Apparatus Organizations (OPD) or Departments. The application functions according to its functional needs after undergoing black box testing. SI SUPER can be developed quickly and flexibly according to user needs using Agile and Laravel development frameworks. It is hoped that the application will help the West Papua local government implements information technology and overcomes problems in the financial sector.